Fatty esteramine production via heterogeneous transesterification of palm based methyl palmitate and triethanolamine / Haliza Abdul Aziz - Haliza, Abdul Aziz (2018)
Fatty esteramine is most significantly used as a precursor in the production of esterquats, a biodegradable cationic surfactant. Preliminary evaluation on fatty esteramine production via heterogeneous transesterification of palm-based methyl palmitate as an alternative to the conventional process using homogeneous catalyst was performed in early part of this study followed by screening of various types of hydrotalcite-like compound (HLTC) used as the heterogeneous catalyst. Prior to the optimization process, preliminary study on the effects of process parameters such as mole ratio of reactants, temperature, vacuum, catalyst dosage, agitator speed and reaction time on conversion of methyl palmitate was performed. Optimization of the operating conditions was conducted via Response Surface Methodology approach. Stability of the HTLC catalyst was evaluated in terms of its reusability and leaching of the active species. This novel heterogeneous transesterification process appeared as a viable route for the production of fatty esteramine as the desired product of mono, di and tri-esteramine were successfully produced. Among the various HTLC investigated, Ca-Al catalyst showed the best catalytic activity towards the transesterification process as it gave the highest conversion of methyl palmitate and yielded fatty esteramine compositions similar to the conventional homogeneous catalyst. Temperature, vacuum and catalyst dosage are among the most significant variables affecting the conversion of methyl palmitate and di-esteramine formation. The optimum reaction conditions obtained from RSM optimization were temperature of 169 oC, catalyst dosage of 0.74%, vacuum of 278.6 mbar and agitation speed of 200 rpm. Ca-Al catalyst was reusable and the conversions as well as fatty esteramine compositions were sustained for three subsequent cycles. Ca-Al exhibited insignificant leaching of the calcium and aluminium active species into the fatty esteramine throughout the recycling process.